2017
DOI: 10.1007/s13300-017-0241-z
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Liraglutide and Lixisenatide in the Treatment of Type 2 Diabetes: Real-World Evidence from The Health Improvement Network (THIN) Database in the United Kingdom

Abstract: IntroductionThe glucagon-like peptide-1 receptor agonists liraglutide and lixisenatide are effective at reducing glycated hemoglobin (HbA1c) levels in patients with type 2 diabetes mellitus (T2DM). Although liraglutide has demonstrated superior efficacy in head-to-head clinical trials, real-world evidence of comparative effectiveness is lacking. This observational study aimed to assess the effectiveness of liraglutide versus lixisenatide in UK clinical practice.MethodsElectronic medical records from The Health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 22 publications
4
8
0
Order By: Relevance
“…In this context, however, our study has confirmed the already well-defined clinical profile of lixisenatide. At the end of our study, 24.8% of patients receiving therapy achieved HbA1c levels below 7.0%, which echoes the response rates seen in the intention-to-treat (ITT) analysis of the GetGoal program with lixisenatide, but exceeds the ones recently reported in a real-life study, where lixisenatide was compared with liraglutide [ 16 ]. Whereas the higher percentage of patients reaching an HbA1c goal below 7% can be explained by the lower baseline HbA1c level in our study [8.7% (72 mmol/mol) vs. 9.5% (80 mmol/mol)], it is noteworthy that the reduction of HbA1c of about 0.7% is comparable in both studies, despite the lower HbA1c in this study.…”
Section: Discussionsupporting
confidence: 74%
“…In this context, however, our study has confirmed the already well-defined clinical profile of lixisenatide. At the end of our study, 24.8% of patients receiving therapy achieved HbA1c levels below 7.0%, which echoes the response rates seen in the intention-to-treat (ITT) analysis of the GetGoal program with lixisenatide, but exceeds the ones recently reported in a real-life study, where lixisenatide was compared with liraglutide [ 16 ]. Whereas the higher percentage of patients reaching an HbA1c goal below 7% can be explained by the lower baseline HbA1c level in our study [8.7% (72 mmol/mol) vs. 9.5% (80 mmol/mol)], it is noteworthy that the reduction of HbA1c of about 0.7% is comparable in both studies, despite the lower HbA1c in this study.…”
Section: Discussionsupporting
confidence: 74%
“…It also has the beneficial effects on the cardiovascular system [ 16 ]. The current study shows liraglutide can reduce the levels of blood glucose, fasting insulin, HOMA-IR, AST, ALT, BUN, TG and TC in the diabetic rats,which is similar to the results of clinical therapy for the diabetic patients [ 17 , 18 ]. The typical pathological characters of atherosclerosis are lipid accumulation, macrophages infiltration, foam cells forming, formation of plaques and thickening of artery intima.…”
Section: Discussionsupporting
confidence: 86%
“…Still the proportion of patients experiencing a 1.0% HbA1c decrease in both cohorts was much smaller compared to our study results. The results from our study are much closer to the retrospective UK cohort study where the proportion of patients with at least 1.0% decrease in HbA1c was 76.0% for liraglutide and 63.6% for lixisenatide [ 14 ]. Still we need to have in mind the higher baseline HbA1c in the UK cohort which would suggest greater glycaemic response.…”
Section: Discussionsupporting
confidence: 80%
“…Moreover in all of the patients continuing lixisenatide treatment the maintenance dose was 20 µg. Another retrospective cohort study evaluating the real-world effectiveness of liraglutide and lixisenatide in UK also showed smaller reductions in HbA1c in T2D patients initiating a GLP-1RA in routine clinical practice [ 14 ]. In that study the observed change in HbA1c for 12 months was − 0.93% with liraglutide and − 0.70% with lixisenatide.…”
Section: Discussionmentioning
confidence: 99%